2022
DOI: 10.1108/rjta-08-2021-0104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weft count and weft density on the surface roughness of 3/1 (Z) twill woven fabric

Abstract: Purpose The purpose of this study is to investigate the effects of weft yarn diameter and pick density on the properties of surface roughness (SMD) of 3/1 (Z) twill-woven fabrics in three measurement directions weft (0°), the warp (90°) and the diagonal (45°). Design/methodology/approach Nine 3/1 (Z) twill samples were prepared with two factors and three levels and their roughness values were measured in the weft (0°), warp (90°) and diagonal (45°) directions of 3/1 (Z) twill fabrics using the Kawabata-FB4 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A factor having an important role in the configuration of the surface characteristics of the fabric is the crimp of the yarns, under the consideration that the yarn densities of warp and weft are of the same class. If the crimp values of the weft and warp yarns are close to each other, the fabric produced is more or less balanced in terms of appearance [8][9][10][11] Modeling is the process of perception of textiles by the skin fills the gap between two contemporary existing solutions: objective and subjective assessment of handling properties of fabrics [12][13][14][15][16]. The different number of mathematical models concerning the human body, clothing, and environment offer useful equations and tools.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A factor having an important role in the configuration of the surface characteristics of the fabric is the crimp of the yarns, under the consideration that the yarn densities of warp and weft are of the same class. If the crimp values of the weft and warp yarns are close to each other, the fabric produced is more or less balanced in terms of appearance [8][9][10][11] Modeling is the process of perception of textiles by the skin fills the gap between two contemporary existing solutions: objective and subjective assessment of handling properties of fabrics [12][13][14][15][16]. The different number of mathematical models concerning the human body, clothing, and environment offer useful equations and tools.…”
Section: Introductionmentioning
confidence: 99%
“…The Kawabata Evaluation System for Fabrics (KESF), Fabrics Analysis by Simple Tests (FAST), and Fabric Touch Tester (FTT) systems are available for measuring the fabric handle-related characteristics under the contact methods. But, as far as the tactile responses are concerned, all the low-stress mechanical characteristics directly or indirectly stimulate the touch pressure roughness and other mechanoreceptors of human skin [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the strength and smoothness also improved greatly due to this blending. According to Beyane et al . (2022), the weft yarn diameter, weft density and the weft diagonal angle affected the surface roughness (SMD) values in KES (Beyene et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…According to Beyane et al . (2022), the weft yarn diameter, weft density and the weft diagonal angle affected the surface roughness (SMD) values in KES (Beyene et al , 2022). This overall blending would be more suitable for winter wear fabric (Das et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They found that surface roughness decreased with increasing fabric density and with decreasing yarn diameters. 17,[19][20][21][22] Researchers explored the effect of different blends of polyestercotton fabrics on the surface property. It was found that a higher presence of polyester fiber in the fabric improves the surface property.…”
mentioning
confidence: 99%